2006
DOI: 10.3748/wjg.v12.i3.408
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein embolization induces compensatory hypertrophy of remnant liver

Abstract: Portal vein branch embolization using absolute ethanol and coil-gelfoam could induce atrophy of the embolized lobes and compensatory hypertrophy of the remnant liver. Gelfoam is an inefficient agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…The use of reversible PVE to ensure vascular occlusion over 2 weeks should therefore induce the required hypertrophy without long-term deleterious effects. Reversible PVE has been used in a few clinical and experimental studies, but was reported to induce insufficient hepatic regeneration [20,21]. This was probably due to early revascularization of the embolized portal branches.…”
Section: Introductionmentioning
confidence: 99%
“…The use of reversible PVE to ensure vascular occlusion over 2 weeks should therefore induce the required hypertrophy without long-term deleterious effects. Reversible PVE has been used in a few clinical and experimental studies, but was reported to induce insufficient hepatic regeneration [20,21]. This was probably due to early revascularization of the embolized portal branches.…”
Section: Introductionmentioning
confidence: 99%
“…Although gelatin sponges are widely available and easy to use for PVE, the recanalization rate after PVE using gelatin sponge in ten dogs was 100% [23], and there have been case reports showing with recanalization following PVE with gelatin sponges [3,4,24]. We found that three of the four patients with recanalized PVs were embolized with gelatin sponges alone, further indicating the need for additional coils following gelatin sponges to prevent recanalization [5,7].…”
Section: Discussionmentioning
confidence: 71%
“…This method has been first applied in a clinical scenario by Makuuchi et al [4] to enhance the safety of extended hepatectomy. Later, the technique has been widely spread in the experimental field as well, especially in large animal models [10,11,12,13] (table 1). …”
Section: Pvo Modelsmentioning
confidence: 99%